Teachers managing the curriculum in the context of the mathematics’ subject group - Nunes, Cláudia (2011)
This study addresses the teacher daily practice. The goal is to understand, from the teachers’ perspective, the challenges and difficulties that they face when attempting to involve the pupils in mathematics learning. We are particularly interested in the issues that arise when teachers assume curriculum management decisions in the con-text of the school mathematics department. The methodology is qualitative and inter-pretive, with case studies. The results indicate that curriculum management sup-ported by the collaborative context creates tensions when a teacher makes decisions that diverge from those assumed collectively and also between the collaborative group with an innovative approach to teaching and teacher professional identity.